THE CURRENT STATUS OF MYOPIA IN CHILDREN AT HANOI EYE HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of myopia and associated factors among 300 children aged 3-18 years presenting to Hanoi Eye Hospital in 2025.Subjects and methods: A cross-sectional descriptive study was conducted on 300 children. Study variables included demographic and clinical characteristics, vision-related lifestyle habits, eye care practices, and the impact of myopia on daily activities.Results: Most children experienced mild impact on daily activities (67%), while 10% were severely affected. Spectacles were the main treatment modality (79.67%); however, 12.67% of children had not received any treatment. The most common duration of electronic device use was 2-4 hours per day (33%), and 39% used devices for more than 4 hours daily. Only 31.66% spent more than 1 hour per day on outdoor activities. Near reading at a close distance was common (81.67%), and 19.33% did not undergo regular eye examinations.Conclusions: Myopia remains prevalent among children and is associated with visual behaviors. These findings highlight the importance of early detection, regular monitoring, and comprehensive interventions to limit progression and prevent complications.
Keywords: Myopia, children, associated factors.